End-to-end encryption scheme for text and media exchange using AESGCM-SIV and elliptic curve diffie-hellman - Akhdan Rafif Nugraha; Nur Widiyasono; Randi Rizal (Institut Teknologi Sepuluh Nopember, 2026)
The exchange of text messages and media files in modern digital communication demands an end-to-end encryption (E2EE) scheme that simultaneously guarantees confidentiality, integrity, authenticity, forward secrecy, and resilience to nonce mismanagement. The widely deployed AES-GCM cipher is known to collapse catastrophically under nonce reuse, enabling plaintext recovery via ciphertext XOR and universal authentication tag forgery, while prior studies have not integrated AES-GCM-SIV, ECDH Curve25519, and HKDF-SHA256 into a unified scheme covering both text and media with comprehensive quantitative measurement. This study aims to design, implement, and evaluate an E2EE scheme based on an ECDH Curve25519, HKDF-SHA256, and AES-256-GCM-SIV pipeline across security and performance dimensions. A quantitative comparative experimental approach was employed using a Rust-based simulation program with 30 iterations per algorithm–data combination across twelve test categories (text of 100–2,000 bytes; image, audio, and video files up to 33.69 MB), accompanied by five security scenarios under the Dolev–Yao threat model (eavesdropping, tampering, replay attack, nonce reuse, and Man-in-the-Middle) and an ablation study of each cryptographic component. The results demonstrate that the proposed scheme satisfies every claimed security property within the defined threat model and tested scenarios, whereas the AES-GCM baseline fails the nonce-reuse scenario. On small data, AES-GCM-SIV incurs a 33.7%–51.6% encryption-time overhead; yet on media files it outperforms the baseline with 11.3%–16.9% higher throughput (peaking at 14.8% on large video), while memory consumption and size overhead remain identical. The ablation study confirms that each component delivers an irreplaceable security contribution. This research contributes empirical evidence that the combination of ECDH Curve25519, HKDF-SHA256, and AES-256-GCM-SIV is a viable cryptographic pipeline for E2EE simulation schemes resilient to implementation errors.